ON-DEMAND RIDE HAILING SERVICES (RHS) FOR COMMUTING PURPOSES: A CASE OF KERALA, INDIA (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The evaluation of the antecedents of users’  continuous usage intention has become essential  for the success of ride hailing services. This  study analysed the antecedent role of customers’  perceptions and satisfaction with continuous  usage intention of ride hailing services in  Kerala, India. The model used in this study  conceptualizes customers perceptions as a  composite variable comprising four dimensions  (perceived usefulness, perceived ease of use,  perceived value and satisfaction) prescribed by  the Technology Acceptance Model (TAM). It  employed a descriptive, correlational survey  approach in which the responses of 216  registered users of ride hailing were analysed  using descriptive inferential statistics. Linear  regression analysis indicated that the model  provided a statistically significant explanation  for the variation in users’ continuous usage  intentions. The study also found empirical  support for customers’ perceptions (perceived  usefulness, perceived ease of use, perceived value  and satisfaction) as antecedents of continuous  usage intention with ride hailing services.
Keywords: Ride hailing; Ride share; Online platform; Technology Acceptance Model (TAM); Continuous usage intention